Chemosensory cues alter earthworm (Eisenia fetida) avoidance of lead‐contaminated soil. (12th October 2016) - Syed, Zuby; Alexander, Dana; Ali, Jasmine; Unrine, Jason; Shoults‐Wilson, W. Aaron
Abstract: Earthworms were shown to significantly avoid soils spiked with Pb at concentrations lower than or comparable to concentrations that demonstrate significant effects for other endpoints. It was also shown that inclusion of a microorganism‐produced volatile compound that attracts earthworms, ethyl valerate, decreased avoidance of spiked soils. These findings suggest that care should be taken when analyzing earthworm avoidance of soils in which microorganism communities are not controlled. Environ Toxicol Chem 2017;36:999–1004. © 2016 SETAC